2011
DOI: 10.1080/00914037.2010.531816
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterizations of Macroporous Poly(acrylamide-2-acrylamido-2-methyl-1-propanesulfonic acid) Hydrogels for In Vitro Drug Release of Ranitidine Hydrochloride

Abstract: Macroporous hydrogels were prepared with acrylamide (AM) and 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) as well as with anhydrous dextrose (AD) as porogen by crosslinking with N,N 1 -methylenebisacrylamide (MBA). The chemical structure of hydrogels is characterized by Fourier transform infrared (FTIR) spectroscopy. Morphological studies done by scanning electron microscopy (SEM) showed the macroporous nature of the hydrogels. Swelling studies of hydrogels were done in distilled water, in aqueous NaCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 32 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…Hydrogels have been used since long in the development of various products of biomedical importance [129,203,204] . Controlled delivery systems are one of such.…”
Section: Applications Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels have been used since long in the development of various products of biomedical importance [129,203,204] . Controlled delivery systems are one of such.…”
Section: Applications Of Hydrogelsmentioning
confidence: 99%
“…Different applications need different properties of polymer construct. Hence, the thorough characterization of the hydrogel matrices is important to determine whether the developed polymer constructs are having suitable properties for desired applications [129] . The current section has been devoted to discuss the various characterization techniques in brief.…”
Section: Gallagher-corrigan Modelmentioning
confidence: 99%
“…In the case of PPAM-4 Ag 0 , characteristic peaks are observed at 3448 cm 21 corresponding to the hydrogen bonded -NH 2 stretching vibrations of AM and MBA units; The peak corresponding to AC5O stretching of amides observed around 1650 cm 21 . The disappearance of peak around 800 cm 21 related to CH2 of sucrose and reduced intensity of C-H stretching peak (2900 cm 21 ) 26 showed that almost all sucrose had leached out. In the case of nonporous Ag NPs hydrogels exhibited similar peaks with a slight difference in their positions.…”
Section: Resultsmentioning
confidence: 99%
“…) 26 showed that almost all sucrose had leached out. In the case of nonporous Ag NPs hydrogels exhibited similar peaks with a slight difference in their positions.…”
mentioning
confidence: 97%
“…DDS can ameliorate the problems of conventional administration by enhancing drug solubility, prolonging duration time, reducing side effect, retaining drug bioactivity and so on [5,6] . A variety of systems such as particulate carriers [7,8] , polymer gels [9][10][11] , lipids [12,13] , etc. have been used as DDSs.…”
Section: Introductionmentioning
confidence: 99%